Analyzing blight impacts on urban areas: a multi-criteria approach - Pinto, A.; Ferreira, F.; Spahr, R.; Sunderman, M.; Govindan, K.; Meidute-Kavaliauskiene, I. (Land Use Policy, 2021)
Often cities are tainted by degraded areas, abandoned and vandalized buildings, and vacant plots, which is commonly called “blight”. Blight is a complex problem with varied consequences requiring integrated decision making at both individual and community levels. This is an important issue since residents of blighted areas live in environments that directly influence their quality of life, values and behaviors. This study conducts an economic, social, and environmental analysis regarding impacts, intermediation and eradication of blight. The complexity of blight requires an analysis encompassing both objective and subjective variables. Also, this study addresses limitations of prior research by applying a methodology that combines cognitive mapping and the decision-making trial and evaluation laboratory (DEMATEL) technique. Study results include a multi-criteria analysis system based on the inputs provided by a panel of experts. Although process-oriented, where results generally are not applicable from one application to another, our approach resulted in blight-caused impacts being allocated to four major clusters: governance; construction and real estate market; social dimensions and security; and health and environment. The findings were presented to and validated by a board member of the Instituto de Habitação e da Reabilitação Urbana (Institute of Housing and Urban Renewal of Portugal). Advantages and limitations of our approach are also discussed.